HUBUNGAN MUTU PELAYANAN TERHADAP MINAT MEMANFAATKAN KEMBALI PELAYANAN DI UNIT RAWAT JALAN RUMAH SAKIT TK. IV MADIUN - Setyawati, Any (LPPM STIKES MUHAMMADIYAH GOMBONG, 2018)
Quality of service and customer satisfaction are key factors affecting the purchase of products or services. Interest visits are influenced by several factors: product quality, cost, promotion, human resources, place and process. Hospital Tk. IV Madiun still has not conducted an optimum service quality evaluation that resulted in a decrease in patient visits and patient complaints regarding services in determining the patient's interest to reuse the services. This purpose to analyzed the relationship of service quality to the interest of re-utilizing the service in the outpatient unit of Madiun Level IV Hospital.Survey with cross sectional approach the process of data retrieval done in the same time between the independent variables and variables bound. With a population of 331 and a sample of 77 respondents. Resulth : The number of respondents was 53.2% female and 46.8% of men, with the highest percentage of age between 36-45 years old 35.1% and the most employed as housewife 26% with secondary education 49.4%. Result of research about service quality that is equal to 76,6% say good, but interest to return low that is 49,4%. Conclusion there was a relationship of service quality to the interest of reusing the service in outpatient Tk Iv Madiun hospital. Key word : customer satisfaction, quality, service,